Anticancer Effects of MAPK6 siRNA-Loaded PLGA Nanoparticles in the Treatment of Breast Cancer - Toruntay, Ceyhun; Poyraz, Fatma Sayan; Susgun, Seda; Yucesan, Emrah; Mansuroglu, Banu (WILEY, 2025)
siRNA-loaded nanoparticles open new perspectives for cancer treatment. MAPK6 is upregulated in breast cancer and is involved in cell growth, differentiation and cell cycle regulation. Herein, we aimed to investigate the anticancer effects of MAPK6 knockdown by using MAPK6 siRNA-loaded PLGA nanoparticles (siMAPK6-PLGA-NPs) in MCF-7 breast cancer cells. After the synthesis and characterisation of nanoparticles, treatment concentrations were determined with cytotoxicity assay. Subsequently, MAPK6 knockdown and anticancer effects of siMAPK6-PLGA-NPs were evaluated by in vitro assays. siMAPK6-PLGA-NPs have been determined to suppress MAPK6 expression efficiently. In vitro studies revealed that siMAPK6-PLGA-NPs significantly reduced the migration, proliferation and colony-forming ability and enhanced the apoptosis in MCF-7 cells. Taken together, siMAPK6-PLGA-NPs exhibited robust and promising anticancer effects against MCF-7 cells. Our findings demonstrated that siRNA-loaded PLGA nanoparticles have great potential for breast cancer treatment and MAPK6 gene may be the therapeutic target in breast cancer.
Keywords: anticancer; breast cancer; MAPK6; PLGA nanoparticle; siRNA; DRUG-DELIVERY; CELL-PROLIFERATION; MECHANISMS; INVASION; PATHWAY; ERK3; Cell Biology; Research & Experimental Medicine